2014
DOI: 10.1111/febs.12769
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of truncated and full‐length glucansucrase GTF180 enzymes from Lactobacillus reuteri 180

Abstract: Glucansucrase enzymes synthesize high-molecular-mass extracellular aglucan polysaccharides from sucrose. Previously, the crystal structure of truncated glucansucrase glucosyltransferase (GTF)180-DN from Lactobacillus reuteri 180 (lacking the N-terminal domain) revealed an elongated overall structure with two remote domains (IV and V) extending away from the core. By contrast, a new crystal form of the a-1,6/a-1,3 specific glucansucrase GTF180-DN shows an approximate 120 o rotation of domain V about a hinge loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 38 publications
7
39
0
Order By: Relevance
“…On the other hand, the full enzyme containing domain V would have a larger glucan‐binding area, thus enabling the stabilization of larger polymer chains. These results are consistent with the experimental observations obtained with the complete and truncated GTF180 enzyme (without the V domain), which revealed that truncation of the enzyme impairs its polysaccharide‐synthesizing ability . Our results are also consistent with a processive enzymatic mechanisms for GTF‐SI, as it generates large‐size glucans without releasing intermediate products.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the full enzyme containing domain V would have a larger glucan‐binding area, thus enabling the stabilization of larger polymer chains. These results are consistent with the experimental observations obtained with the complete and truncated GTF180 enzyme (without the V domain), which revealed that truncation of the enzyme impairs its polysaccharide‐synthesizing ability . Our results are also consistent with a processive enzymatic mechanisms for GTF‐SI, as it generates large‐size glucans without releasing intermediate products.…”
Section: Resultssupporting
confidence: 92%
“…The position of domain V shows a shift of about 20 Å in GTFA‐ΔN compared to GTF180‐ΔN, whereas in ΔN123‐GBD‐CD2 of DSR‐E this domain adopts a completely different position close to the catalytic core, resulting in a more compact enzyme structure . The intrinsic flexibility of domain V has been related to the GTF180 functioning, as this domain may facilitate glucan synthesis by bringing the polysaccharide chains toward and away from the catalytic site . Additionally, the flexibility of domain V in GTF180 has been related to the ionic strength conditions under which crystallization takes place, as observed in the case of L. reuteri N‐terminally truncated glucansucrase GTF‐180 in its orthorhombic apo‐form (PDB code 4AYG), in which high ionic strength conditions lead to a more curved conformation of domain V compared to the 3HZ3 model .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domain V, representing the truncated GBD, is the most distant from the active site. This domain adopts variable positions in GTF180-⌬N glucansucrase due to motions around a hinge located between domains IV and V (38). The branching sucrase ⌬N 123 -GBD-CD2 derived from the bi-functional glucansucrase DSR-E from Leuconostoc citreum NRRL B-1299 (formerly Leuconostoc mesenteroides NRRL B-1299) has its domain V interacting with the domain IV and shows a more compact structure than GTF180-⌬N (9).…”
mentioning
confidence: 99%
“…Purification of the enzyme could easily be achieved by affinity chromatography over Sephadex (cross-linked dextran), but the dextran used for elution could not be completely removed by subsequent diafiltration. Glucansucrases are often described based on amino acid alignments with other glucansucrase as having an Nterminal variable region, followed by a catalytic domain, and a C-terminal glucan-binding domain (Monchois et al 1999); however, structural analyses show that the protein actually contains five domains (A, B, C, IV, and V) that are formed through a U-shape configuration that involves two regions of the polypeptide for each domain, with the exception of domain C (Ito et al 2011;Meng et al 2015;Pijning et al 2014;Vujicic-Zagar et al 2010). Numerous studies have examined glucan-binding of the C-terminal repeat domain (Haas and Banas 2000;Kingston et al 2002;Monchois et al 1998;Shah et al 2004), which likely binds tightly to regions of α(1→6) in a strongly exothermic reaction (Komatsu et al 2011).…”
Section: Discussionmentioning
confidence: 99%